2011
DOI: 10.1071/rd10183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the uterine environment early in pregnancy establishment to characterise cows with a potentially superior ability to support conceptus survival

Abstract: Abstract. During previous investigations, the capacity of the cow to secrete prostaglandin in response to oxytocin has been linked with pregnancy outcome. The objective of the present study was to evaluate the predictive value of prostaglandin release to identify groups of cows as potentially superior (SR, low prostaglandin release) or inferior (IR, high prostaglandin release) for pregnancy outcome and to utilise these cows to investigate factors that contribute to optimum uterine conditions for early pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 60 publications
1
12
1
3
Order By: Relevance
“…Regarding SERPINA14, it is one of the most abundant proteins present in the pregnant ruminants uterus (Segerson and Bazer 1989). Its main functions are immune modulation and transport of proteins such as immunoglobulins (Ulbrich et al 2009a;Padua and Hansen 2010;Ledgard et al 2011). A previous study (Bauersachs et al 2005) reported that the expression of SERPINA14 is increased at late dioestrus compared with early dioestrus, indicating that the main function of SERPINA14 could be much later during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding SERPINA14, it is one of the most abundant proteins present in the pregnant ruminants uterus (Segerson and Bazer 1989). Its main functions are immune modulation and transport of proteins such as immunoglobulins (Ulbrich et al 2009a;Padua and Hansen 2010;Ledgard et al 2011). A previous study (Bauersachs et al 2005) reported that the expression of SERPINA14 is increased at late dioestrus compared with early dioestrus, indicating that the main function of SERPINA14 could be much later during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…In cattle, ULF is a prerequisite for development of the embryo beyond the hatched blastocyst stage in vivo, and attempts to artificially induce elongation of bovine conceptuses in vitro have been unsuccessful [9], [10]. The ULF of ruminants is composed of both secreted and transported molecules that include numerous secreted proteins [11], [12], glucose [13], ions [13], fatty acids [14] and amino acids [13], [15]. In sheep, a significant increase in total amino acid content occurs between Days 10 and 16 of pregnancy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similar classes of genes were identified in another model of fertility where endometrial gene expression was compared between post partum dairy cows with mild (good pregnancy outcome) versus severe (poor pregnancy outcome) negative energy balance. The increased expression of alpha-2-HS-glycoprotein; AHSG, MMP1, MMP3, MMP9 and MMP13 in cows with severe negative energy balance are possible markers of a compromised uterine environment [67], while increased secreted phosphoprotein 1; SPP1 was a marker of reproductive superiority in heifers following an oxytocin challenge in vivo [68]. The use of large-scale transcriptional analysis in these and other studies will continue to allow the detection of an optimal versus a compromised uterine environment.…”
Section: Other Models Of Uterine Receptivitymentioning
confidence: 99%